Pengaruh Content Marketing dan Celebrity Endorser Terhadap Keputusan Pembelian Dengan Brand Trust Sebagai Variabel Intervening: Studi pada Pembeli Hafez Restorer di Media Sosial Tiktok - Abdur Rohman; Antin Rakhmawati (Economic Reviews Journal, 2024)
The rapid development of digital technology has made social media one of the most influential platforms in the purchasing decision process. TikTok is one of the social media platforms currently popular in Indonesia. The presence of TikTok has attracted many companies to start utilizing it as a marketing tool. The purpose of this research is to examine the influence of Content Marketing and Celebrity Endorsement on purchasing decisions for Hafez Restorer products on TikTok, with Brand Trust as an intervening variable. The research method used is quantitative, with data analysis techniques involving path analysis. The sampling method employed purposive sampling with 106 respondents. Data processing was carried out using SPSS software version 22. The results of the study indicate that the variables of Content Marketing and Celebrity Endorser have a positive and significant effect on Brand Trust. Additionally, Content Marketing and Celebrity Endorser have a positive and significant effect on Purchasing Decisions, and Brand Trust positively and significantly affects Purchasing Decisions. Furthermore, Content Marketing and Celebrity Endorser indirectly influence purchasing decisions through Brand Trust as an intervening variable.